Odpowiedzi

2010-02-24T13:52:27+01:00
A)x=1 7/8-9
x=15/8- 9
x=15/8 - 72/8
x= - 57/8
x=7 1/8
b)- 8y=5 /:-8
y=-5/8
c)x=4/5+4/5
x=8/5
x=1 3/8
(bo 0,8=8/10=4/5)
d)6 1/8y= 1/: 6 1/8
y=1/:49/8
y=1*8/49
y=8/49
e)x=6,1+2,2
x=8,3
f)y=10*1/3
y=10/3
y=3 1/3
g)8a=36-4=
8a=32 /:8
a=4
h)8/9 k=3 -1/3
8-9k= 2 3/3-1/3
8/9k= 2 2/3/ *9/8
k= 8/3 * 9/8
k=3
i)6b=10+3
6b=13/:6
b=13/6
b= 2 1/6
j) -1/4 l= 9/4+3/4
-1/4l= 12/4 /*-4
l=-12
k)-2,5c=17+8
-2,5c=25/ 2 1/2
c= 25/ 5/2
c=25 * 2/5
c=10
l) 0,4m=-6+2
0,4m=-4 /:0,4
m=4/10:-4
m=10/4 * -4
m= -10
34 4 34
2010-02-24T13:52:40+01:00
A)9+x=1 ⅞
x = 1⅞ - 9
x = -7⅛

b)-8y=5 / :(-8)
y = -⅝

c)x-⅘=0,8
x = ⅘+⅘
x = ⁸/₅
x = 1 ⅗

d)6 ⅛y=1
⁴⁹/₈y=1 / * (⁸/₄₉)
y = ⁸/₄₉

e)-2,2+x=6,1
x = 6,1+2,2
x = 8,3

f) -⅓y=10 / *(-3)
y = -30

g)8a+4=36
8a =36-4
8a = 32/ : 8
a = 4

h)⁸/₉k+⅓=3
⁸/₉k = 3 -⅓
⁸/₉k = 2⅔ /* (⁹/₈)
k = ⁸/₃ * (⁹/₈)
k = 3

i)6b-3=10
6b = 10+3
6b = 13 / :6
b = ¹³/₆
b = 2⅙

j)-¾ - ¼l=2,25
- ¼l = 2,25 + ¾
- 0,25l = 2,25 +0,75
-0,25l = 3 / :(-0,25)
l= -12

k)-2,5c-8=17
-2,5c = 17+8
-2,5c = 25 /: (-2,5)
c= -10

l)0,4m-2= -6
0,4m = -6+2
0,4 m = -4 / : 0,4
m = -10
8 3 8
2010-02-24T13:59:05+01:00
A)
9+x=1 7/8
x=1⁷/₈-9
x=-7⅛

b)
-8y=5
y=-⅝

c)
x-4/5=0,8
x=0,8+0,8
x=1,6

d)
6 1/8y=1
y=8/49

e)
-2,2+x=6,1
x=6,1+2,2
x=8,3

f)
-1/3y=10
y=-30

g)
8a+4=36
8a=36-4
8a=32
a=4

h)
8/9k+1/3=3
8/9k=3-⅓
8/9k=2⅔
k=3

i)
6b-3=10
6b=10+3
6b=13
b=2⅙

j)
-3/4 - 1/4l=2,25
-1/4l=2,25+3/4
-1/4l=3
l=-12

k)
-2,5c-8=17
-2,5c=17+8
-2,5c=25
c=-10

l)
0,4m-2= -6
0,4m=-6+2
0,4m=-4
m=-10
7 2 7